Sequential blind beamforming algorithm using combined CMA/LMS for wireless underground communications - Fares, S.A.; Denidni, T.A.; Affes, S. (2004 IEEE 60th Vehicular Technology Conference, 2004)
In this contribution, we propose a new smart antenna array (SAA) structure using sequential blind beamforming for multipath correlated signals in an underground mining environment. This adaptive receiver is dedicated to underground environments, where the multipath problem is more severe than the co-channel interference. In this confined area, the received path arrivals are not only highly correlated but actually belong to the same signal source. Consequently, we exploit the idea that these arrival paths are delayed replicas from an identical source. Simulation results confirm the effectiveness of the proposed blind beamformer. It outperforms the CMA beamformer by approximately 2.5 dB and 4.1 dB for Gaussian and Rayleigh channels, respectively.